New findings of oribatid mites of the genus Suctobelbella (Acari: Oribatida: Suctobelbidae) from Korea - Bayartogtokh, Badamdorj; Bae, Yang-Seop (Zootaxa, 2024)
The genus Suctobelbella is diversely represented in the northern hemisphere, but this group is insufficiently studied in Korea. Herein, we propose two new species, Suctobelbella (Flagrosuctobelba) subiasi sp. nov., Suctobelbella (Ussuribata) wiryeca sp. nov., and provide supplementary descriptions of two known species, Suctobelbella (Flagrosuctobelba) hastata Pan’kov, 1986 and Suctobelbella (Flagrosuctobelba) plumosa Chinone, 2003, which are reported from Korea for the first time. Diagnostic characterization and illustration of each species along with their habitat ecology and distributional data are given. Furthermore, a diagnostic key for the identification of adults of the known species of Suctobelbella in Korea, is provided.